The given quadratic equation is:
\[ x^2 + 4x + 3 = 0 \]
In the standard form of a quadratic equation \( ax^2 + bx + c = 0 \), the coefficients are identified as follows:
- \( a \) is the coefficient of \( x^2 \), which is 1 in this case.
- \( b \) is the coefficient of \( x \), which is 4 in this case.
- \( c \) is the constant term, which is 3 in this case.
To find one solution to the equation, we can either factor it or use the quadratic formula. The equation factors to:
\[ (x + 1)(x + 3) = 0 \]
Setting each factor to zero:
- \( x + 1 = 0 \implies x = -1 \)
- \( x + 3 = 0 \implies x = -3 \)
One solution to the equation could be -1 or -3.
So the completed statements are:
The value of a is 1.
The value of b is 4.
The value of c is 3.
One solution to the equation is -1 (or you could also state -3).